CONSUMER EMPOWERMENT: A SOURCE OF CO-CREATION OF VALUE - ABDELLATIF CHAKOR (Université Mohammed V de Rabat, 2020)
The objective of this article is to clarify, through a literature review, another trend practiced by many companies through which they produce their products and services. It is mainly the delegation of power to consumers to participate in the creation of business offers according to their expectations. This new trend manifests itself by the use of empowerment strategies (Denegri-Knott et al. 2006) that are recently adopted by a set of companies in their value co-creation approach. With the evolution of new digital technologies, the passive consumer of the 80s has become a consum'actor (Badot and Cova, 1992), in other words, an active consumer, actor of his own consumption and his own choices. This fact leads the companies of nowadays to delegate a set of tasks, due to the opportunities offered by new digital technologies in order to benefit from the skills of consumers to co-create together products according to their expectations. While involving the consumer in their process of value creation, who's the cardinal purpose is to defend a new marketing orientation that asserts that the customer is not only an individual with needs to be satisfied, but also an agent acting with skills that can co-create value and/or experience (Prahalad and Ramaswamy, 2004) according to the new SDL logic (vargo and luch 2004)